2017
DOI: 10.1007/s40097-017-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

SnO2 nanoparticles as an efficient heterogeneous catalyst for the synthesis of 2H-indazolo[2,1-b]phthalazine-triones

Abstract: A new protocol for the synthesis of 2H-indazolo[2,1-b]phthalazine-trione derivatives is described via a one-pot three-component condensation reaction of phthalhydrazide, dimedone or 1,3-cyclohexanedione and aromatic aldehydes catalyzed by SnO 2 nanoparticles as a heterogeneous catalyst under solvent-free conditions. The SnO 2 nanoparticles (NPs) were characterized by FT-IR, X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and energy dispersive X-ray analyzer (EDAX). The advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The SnO 2 /C-n catalysts were synthesized by a one-step sintering process at 300 °C in air for 12 h, as illustrated in Figure 1a. 40 The amount of the SnCl 2 precursor was changed while keeping the carbon content constant during the preparation. The crystalline structure of SnO 2 /C-n was then characterized by XRD measurements (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The SnO 2 /C-n catalysts were synthesized by a one-step sintering process at 300 °C in air for 12 h, as illustrated in Figure 1a. 40 The amount of the SnCl 2 precursor was changed while keeping the carbon content constant during the preparation. The crystalline structure of SnO 2 /C-n was then characterized by XRD measurements (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…443 Tin oxide nanoparticles are reported to be an efficient heterogeneous catalyst for the synthesis of 2H-indazolo[2,1-b]phthalazine-triones. 444 Bismuth oxide nanoparticles of stoichiometry Bi 2 O 3 with sizes of less than 10 to hundreds of nanometers were obtained by Scalese and co-workers, using 355 nm, 5 ns pulsed laser ablation of a Bi 2 O 3 colloid in ethanol. 445 A mixture of Bi, monoclinic α-Bi 2 O 3 and tetragonal β-Bi 2 O 3 of average sizes of 30−55 nm was prepared by 1064 nm, 12 ns pulsed laser synthesis from a metallic Bi target in methanol, ethanol, or ethyl methyl ketone by Delavari et al 105 Bismuth oxide catalysts found uses for the reduction of NO with hydrocarbons, allylic oxidations, acetalization and ketalization of carbonyls with diols, for catalytic soot combustion, and as catalyst support material.…”
Section: Oxidesmentioning
confidence: 99%
“…Small 2–6 nm SnO 2 nanoparticles were created by Sasaki et al by 355 nm, 7 ns pulsed laser ablation of an Sn plate in aqueous SDS solution . Tin oxide nanoparticles are reported to be an efficient heterogeneous catalyst for the synthesis of 2 H -indazolo­[2,1- b ]­phthalazine-triones …”
Section: Outlook: Pulsed Laser In Liquids Made Nanomaterials As Poten...mentioning
confidence: 99%
“…[15][16][17][18][19] More specifically, they have been investigated in a variety of organic synthesis reactions due to high catalytic activity, selectivity, and stability. For example, SnO 2 NPs have been served as a heterogeneous catalyst in coumarins, 20 imidazole derivatives, 21 benzimidazoles, 22 2H-indazolo [2,1-b] phthalazine-triones, 23 synthesis of 4, 5-dihydropyrrolo [1, 2-a] quinoxalines 24 reduction, coupling, cycloaddition reactions, among others. Hence, the versatility and effectiveness of SnO 2 nanocatalysts are deemed a promising tool for achieving more sustainable and environmentally friendly chemical processes.…”
Section: Introductionmentioning
confidence: 99%